Global South Asians introducing the modern diaspora - Brown, Judith M. 1944- (Cambridge University Press, 2006)
By the end of the twentieth century some nine million people of South Asian descent had left India, Bangladesh or Pakistan and settled in different parts of the world, forming a diverse and significant modern diaspora. In the early nineteenth century, many left reluctantly to seek economic opportunities which were lacking at home. This is the story of their often painful experiences in the diaspora, how they constructed new social communities overseas and how they maintained connections with the countries and the families they had left behind. It is a story compellingly told by one of the premier historians of modern South Asia, Judith Brown, whose particular knowledge of the diaspora in Britain and South Africa gives her insight as a commentator. This is a book which will have a broad appeal to general readers as well as to students of South Asian and colonial history, migration studies and sociology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; South Asian diaspora; Südasiaten; Migration; Ausland; South Asians / Migrations